Perception of Traditional Parenting on Adolescents’ Psychological Well-Being: The Value of “Mon Niku Kawai Handak Nyak Kawai Handak Munih” - Apriani, Miki; Suryaratri, Ratna Dyah; Fajar Rakhman, Gumgum Gumelar; Akbar, Zarina; Ariyani, Mira; Maulana, Herdyan (Biopsikososial: Jurnal Ilmiah Psikologi Fakultas Psikologi Universitas Mercubuana Jakarta, 2025)
This study aims to explore the influence of traditional parenting styles based on the local cultural value of “Mon Niku Kawai Handak Nyak Kawai Handak Munih” on the psychological well-being of adolescents. This value emphasizes balance in social relationships and serves as a fundamental principle in traditional parenting practices in Ogan Komering Ulu Timur. The sample consisted of 118 adolescents aged 12–21 years, selected using purposive sampling techniques. The instruments used included the Parental Authority Questionnaire (PAQ) and Ryff’s Psychological Well-Being Scale. Data were analyzed using simple linear regression JASP software. The results showed a significant influence of traditional parenting styles on psychological well-being. Proportional implementation of traditional parenting styles can improve dimensions of positive relationships with others and self-acceptance. This study provides important insights into parenting practices within the context of local culture, serving as a reference for developing interventions to enhance adolescents’ psychological well-being and contributing to the cross-cultural psychology literature.